A Kinetics study of 2-ethyl-2-hexenal hydrogenation to 2-ethyl-hexanol over Nickel based catalyst. (June 2019) - Virgana, S; Subagjo; Gunawan, M L
Abstract: The 2-ethyl-hexanol was much-needed in the plasticizer industry as a precursor for the synthesis of bis diesters (2-ethyl hexyl) phthalate (DEHP). This compound can be synthesized by oxo reaction, where one of the steps isa consecutive hydrogenation of the 2-ethyl-2-hexenal to 2-ethyl-hexanol. This reaction required metal-based catalyst. This research aimed to develop the formula and procedure of catalyst synthesized and get a kinetics of the reaction. The catalyst was synthesized with a nickel content of 50%-w. The support consists of γ-alumina and SiO2 (cab-osil) in variations of 0%-w up to 100 %-w of cab-o-sil towards support. The activity of synthesized catalysts were tested at 120°C and 30 bars in the fixed bed reactor. The results showed that the best performing catalyst was NiO50-Cab50 with 98.29% 2-ethyl-2-hexenal conversion and selectivity to 2-ethyl-hexanol 87.41 %. By varying the reaction temperature of 100-120°C in the best catalyst, it is found that the consecutive reaction was the first order with the activation energy of 2-ethyl-2-hexenal hydrogenation to 2-ethyl-hexanal was 33.66 kJ/mol and hydrogenation 2-ethyl-hexanal to 2-ethyl-hexanol was 58.39 kJ/mol. This showed that the hydrogenation of C = C bonds was easier than the C = O bond.